Gas-chromatographic determination of nitrophenols after derivatisation with diazomethane - Nick, Klaus; Schöler, Heinz Friedrich (Fresenius' journal of analytical chemistry, 1992)
A method is described to determine nitrophenols and two herbicides (Bromoxynil, Ioxynil) in precipitation, with GC-PND and GC-MS. First, the micropollutants were extracted by a mixture of pentane and ether (1/1), concentrated by rotary evaporator, then methylated by diazomethane. The extraction and reaction yields were measured. The resulting recoveries were between 75 and 100% for the mononitrophenols and about 70% for methylnitrophenols. The detection limits were about 0.25 ~tg/1for most substances.
Gesehen am 03.04.2023